2005
DOI: 10.1016/j.eurpsy.2004.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use in schizophrenia: a study of cotinine concentrations in the saliva of patients and controls

Abstract: Nicotine has been proposed to provide anxiety relief, oral gratification and self-medication of psychotic symptoms in psychiatric patients. In order to investigate the relations between psychopathology and tobacco use we measured the concentration of cotinine, the major metabolite of nicotine, in the saliva of psychiatric patients and healthy volunteers. In a sample of 42 schizophrenic patients we correlated smoking status, cotinine levels, symptom profiles (PANSS), and neuroleptic side effects (Simpson-Angus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
3
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 28 publications
7
44
3
1
Order By: Relevance
“…Our finding of a higher plasma cotinine level per cigarette smoked (cotinine/CPD ratio) is consistent with earlier studies that reported higher urinary, plasma and saliva cotinine levels (Olincy et al, 1997;Sacco et al, 2005;Strand and Nybäck, 2005;Williams et al, 2005) and greater reward value (Spring et al, 2003) in SS. Olincy et al (1997) found no differences between groups in urinary cotinine clearance, while Williams et al (2005) showed that the ratio of 3-hydroxycotinine (a metabolite of cotinine) to cotinine was not altered in SS suggesting increased nicotine intake rather than alterations in nicotine metabolism.…”
Section: Baseline Differencessupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding of a higher plasma cotinine level per cigarette smoked (cotinine/CPD ratio) is consistent with earlier studies that reported higher urinary, plasma and saliva cotinine levels (Olincy et al, 1997;Sacco et al, 2005;Strand and Nybäck, 2005;Williams et al, 2005) and greater reward value (Spring et al, 2003) in SS. Olincy et al (1997) found no differences between groups in urinary cotinine clearance, while Williams et al (2005) showed that the ratio of 3-hydroxycotinine (a metabolite of cotinine) to cotinine was not altered in SS suggesting increased nicotine intake rather than alterations in nicotine metabolism.…”
Section: Baseline Differencessupporting
confidence: 93%
“…Several studies have suggested that smokers with schizophrenia had higher levels of urinary (Olincy et al, 1997), saliva (Strand and Nybäck, 2005), and plasma cotinine Williams et al, 2005) than control smokers despite no significant difference in daily smoking or urinary cotinine clearance (Olincy et al, 1997), or in metabolism of cotinine (Williams et al, 2005). A recent study suggesting differences in smoking topography in smokers with schizophrenia versus controls provides physiological support for increased nicotine intake (Tidey et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A world-wide meta-analysis of smoking and schizophrenia demonstrated three times greater smoking in schizophrenia than in the general population and twice the incidence compared with other major mental illnesses regardless of antipsychotic drug use [19]. It has also been shown that patients with schizophrenia smoke cigarettes much more intensively thereby increasing their nicotine intake with higher antipsychotic doses generally related to greater smoking [20]. Highly dependent smokers are in general those with more severe schizophrenic illness in patients taking antipsychotic drugs [21].…”
Section: Nicotinic Systems and The Cognitive Impairment Of Schizophreniamentioning
confidence: 99%
“…These latter results are corroborated by biochemical measures of smoke intake. In four studies, those with mental illness had saliva or plasma cotinine levels averaging 44% higher than in general population controls [3][4][5][6]. Other studies have shown consistently higher scorers on questionnaire measures of nicotine dependence [3,[7][8][9].…”
mentioning
confidence: 95%